COMPORTAMENTO DE CULTIVARES DE ALFACE EM FUNÇÃO DO ESPAÇAMENTO - Echer, Márcia de Moraes; Sigrist, José Maria M.; Guimarães, Vandeir Francisco; Minami, Keigo (REVISTA DE AGRICULTURA, 2015)
COMPORTAMENTO DE CULTIVARES DE ALFACE EM FUNÇÃO DO ESPAÇAMENTO